A case of new-onset Fulminant type 1 diabetes after secondary SARS-CoV-2 infection - Jie Wang; Yiwen Huang; Feng Tao (Heliyon, 2024)
Fulminant type 1 diabetes is a subtype of type 1 diabetes characterised by a rapid progression to diabetic ketoacidosis combined with a background of rapid and almost complete pancreatic islet destruction. FT1D induced by secondary SARS-CoV-2 infection is rare. Herein, we present the case of a 42-year-old male patient with new-onset FT1D after a secondary SARS-CoV-2 infection, with recurrent hyperglycaemia and ketosis as the primary manifestations. Eventually, the patient responded well after receiving more than 50 units of insulin daily. This case illustrates the importance of paying attention to severe hyperglycaemia accompanying recurrent ketosis, particularly among patients with secondary SARS-CoV-2 infection.